Evaluation of a Mobile App to Assist Patient Education and Research in Arthroplasty - Leina Suzuki, BE(Hons); Francis Connon, MBBS, FRACS; Selin Munir, PhD; Sarah Piplica, BHlthSci, MPH; Hemant Pandit, FRCS (Orth), D Phil (Oxon); Daevyd Rodda, MBBS, FRACS (Arthroplasty Today)
Background: Paper-based patient-reported outcome measures (PROMs) and patient education can assist in improving outcomes but is administratively burdensome. Mobile phone applications (‘apps’) can distribute extensive information and PROMs at relevant time points. This study aimed to assess the suitability of an app to guide postoperative management and record PROMs based on satisfaction and compliance. Methods: Thirty-four patients who were scheduled for a total hip/knee arthroplasty were enrolled into the study. Automatic notifications were sent by the app to complete PROMs at the appropriate time points. Patients were reminded via phone call if PROMs were not completed. An app satisfaction questionnaire was also completed, where a high score represented satisfaction with the app. Results: Patients remained satisfied with the app throughout the study with a mean score of 19.0 out of 25. 57% found the app to be helpful with completing surveys, with 63% preferring the app over paper handouts. Majority of the participants (68%) stated that they would use the app again. There was an overall mean compliance of 78% at all time points. Most patients (82%) required at least one phone call reminder, with 18% of patients completing their PROMs prompted by the app notification alone. Conclusions: A mobile phone app can be useful for both distributing patient education and collecting PROMs. PROMs collected using a mobile phone app still caused some administrative burden with many participants requiring multiple reminders to complete their questionnaires. While paper-forms will still be required for some patients, most found the app preferable to paper-form.